Exploration of Physics Concepts in Local Wisdom of South Sumatera as an Effort to Develop Students' 21st-Century Skills - Wiyono, Ketang; Ismet, Ismet; Andriani, Nely; Fitonia, Alika; Nadia, Hartisya; Meitasari, Diana; Nazhifah, Nauratun (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This research aims to identify physics concepts in South Sumatera's local wisdom. South Sumatera is one of the provinces in Indonesia with a very high level of diversity. The heterogeneous geographical and socio-cultural conditions in South Sumatera provide a strong background for linking the local wisdom of the area with physics learning. The research was carried out using observations, interviews, and documentation. The process revealed a connection between various local wisdoms in South Sumatera and various concepts in physics. Some of the identified local wisdoms include typical South Sumatera food, the environment around the Musi River, and typical South Sumatera buildings. The barges adhere to Archimedes' Law principles. Temperature and phase changes are closely related to the pempek making process. Making smoked fish uses the concepts of temperature and heat. Making salted fish utilizes the concept of heat transfer by radiation and evaporation. The process of making Kemplang closely aligns with the concepts of heat transfer, evaporation, and expansion. This local wisdom, when used as an object in physics learning, is highly suitable and relevant to the Merdeka Curriculum. In this way, students will more easily understand the learning they are doing.